Teaching EFL Students in Post-Pandemic Era: ICT Tools and Obstacles - Erfin Wijayanti; Anggit Prasetio Nugroho; Andi Miftahul Maulidil Mursyid; Rahmawansyah Rahmawansyah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research discovered how the Information and Communication Technology (hereinafter, ICT) tools were used and the obstacles faced in English language teaching after the pandemic. This research used quantitative methods to gather the data. The data was obtained by administering a questionnaire and sharing via Google form with 40 students of the English Department at the State Islamic Institute in Papua. The results of this study indicate that students majoring in English at the Papua State Islamic Institute use two categories of ICT in the learning process, namely web-based learning and non-web-based learning. Web-based learning ICT Tools used are the Internet as the connection as well, YouTube, ZOOM Meeting, WhatsApp, Mobile Phones, and Computer or Laptop. Meanwhile, non-web-based learning ICT Tools used are language Lab, Overhead Projectors, and Films. The ICT Tools used are language lab and overhead projectors. The obstacles faced by the students are Lack of Effective Training, Limited accessibility, and network connection, a school with limited technical support, limited time, and lack of lecturers' competency. The biggest problem reached 59.30% with limited accessibility and network connection and school with limited technical support. This means English Department at State Islamic Institute in Papua has a low internet connection and insufficient computer and software to access.